Effects of crushed stone dust on some properties of concrete - Çelik, Tahir; Marar, Khaled (Elsevier, 1996)
Crusher dust is a fine material formed during the process of comminution of rock into crushed stone or crushed sand. This dust is composed by particles which pass 75 μm BS sieve. Effects of dust content in aggregate on properties of fresh and hardened concrete are not known very well. An experimental study was undertaken to find out the effects of various proportions of dust content on properties of fresh concrete and hardened concrete.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/0008-8846(96)00078-6) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Crushed Stone; Dust; Concrete